2017
DOI: 10.1097/mog.0000000000000347
|View full text |Cite
|
Sign up to set email alerts
|

Update in HIV–hepatitis C virus coinfection in the direct acting antiviral era

Abstract: Purpose of Review Availability of direct acting antivirals (DAAs) that demonstrate remarkable clinical efficacy and safety has revolutionized the ability to treat chronic infection with hepatitis C virus (HCV). An equal measure of clinical success has now been achieved in persons co-infected with HCV and the human immunodeficiency virus (HIV), a historically harder to cure cohort with interferon-based therapy. Global goals include identifying all HIV/HCV-infected persons, gaining access to DAA-therapy, prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 92 publications
0
20
0
Order By: Relevance
“…[45,46] Possible barriers to a successful HCV response in PLWH include access to medical care, timely diagnosis of HIV/HCV and initiation of DAA therapy, costs associated with therapy, underinsured status, longer time needed for screening HIV/HCV and time required for counseling. [5,47] Achieving SVR12 has also been shown to affect quality of life (QoL) in patients with HIV/HCV coinfection. Prior to DAA therapy availability, QoL reported by patients with HIV/HCV coinfection was significantly lower than in HIV mono-infected patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[45,46] Possible barriers to a successful HCV response in PLWH include access to medical care, timely diagnosis of HIV/HCV and initiation of DAA therapy, costs associated with therapy, underinsured status, longer time needed for screening HIV/HCV and time required for counseling. [5,47] Achieving SVR12 has also been shown to affect quality of life (QoL) in patients with HIV/HCV coinfection. Prior to DAA therapy availability, QoL reported by patients with HIV/HCV coinfection was significantly lower than in HIV mono-infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Nearly 75% to 82% of PLWH who inject drugs are also infected with HCV. [2,4,5] Prior to potent combination antiretroviral therapy (ART), early studies suggested that progression to fibrosis is accelerated in patients with HIV/HCV coinfection. Factors affecting disease progression in this population include increased alcohol use, older age, longer duration of HCV infection, and immunosuppression (CD4 < 200 cells/mm 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The achievement of sustained virological response 12 weeks after completion of treatment (SVR12) has been associated with improved liver function, decreased clinical complications and all-cause mortality [7][8][9][10]. With regard to HIV coinfection, inferior treatment response in patients with HIV is no longer a concern and regimens proven efficacious in HCV monoinfection are widely applicable to patients with HIV [11]. However, little is known about whether HIV coinfection modifies outcomes of HCVrelated liver disease after achieving SVR.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that despite the reduction of HIV infection among PWID almost all HIV positive PWID are still infected with HCV suggesting that decline of HCV infection among PWID can only been achieved by significant reduction of circulation of HCV in the community. It is hoped that this will happen after new DAAs for treatment of chronic HCV infection are made available to all patients including PWID and HIV/HCV co-infected patients (25,26). According to our study as of end of 2015 only 5% of patients with HCV were receiving anti-HCV treatment similar to other Eastern European countries (27,28).…”
Section: Discussionmentioning
confidence: 71%